Ayurvedic Management of Vipadika (Palmoplantar psoriasis): A Case Report (AYUSHDHARA, 2023)
Vipadika is one among the Kshudra Kushta. It features with Panipada sphutana, Teevravedana. Its symptoms can be correlated with palmoplantar psoriasis, which is a form of psoriasis and is chronic and recurring in nature that affects the palms and soles of the feet and is characterized by hyperkeratosis, fissures, erythema and occasionally inflammation and pustules. This disease not only affects person physically but also affects the mental and social health of the patient. Since there is no satisfactory treatment for psoriasis in conventional medicine. Ayurvedic treatment can provide promising results in this condition. In this article a case of 50 years old female with a complaints of Peeling of the palmoplantar skin and Itching with occasional burning sensation in the palmoplantar region since 3-4 months is presented which was successfully treated with Shamanoushadis like Manjishtadi Kashaya, Nimbadi Guggulu, Navayasa Loha, Kamaduga Rasa and external application of Jeevantyadi Yamaka lepam for a period of one month. This is an effort to show the brighter side of Ayurvedic interventions not just in alleviating the symptoms but also in improving the immune strength and causing no recurrence of disease.